THE CORELATION BETWEEN STUDENTS’ READING HABIT AND THEIR WRITING ABILITY - Siska Oktawidya Wati (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2021)
This research was a correlation study which aims to determine the correlation between srudents’ reading habit and their writing ability in Teaching English Learning. There were two variables in this study, reading habit and writing ability. The population of the study were the X grade students of SMAN 2 Batusangkar in the academic year 2020/2021. The sample technique in this research used cluster random sampling from 356 students selected for class X MIPA 2 with 36 students. This study used the Product Moment formula to determine the coefficient correlation and t-test to found out the significance correlation between students’ reading habit (X) and their writing ability (Y). The result showed that the t-observed was (4.01) and t-table was (1.70) in significance level of 5% (0,005), so t-observed was bigger than t-table then Ha was accepted and Ho was rejected. Thus, it can be concluded that there was a correlation between students’ reading habit and their writing ability in descriptive text at the X grade of SMAN 2 Batusangkar